2016
DOI: 10.1681/asn.2015010061
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Lithium Use and Risk of Renal and Upper Urinary Tract Cancers

Abstract: Lithium induces proliferation in the epithelium of renal collecting ducts. A recent small-scale cohort study reported a strong association between use of lithium and increased risk of renal neoplasia. We therefore conducted a large-scale pharmacoepidemiologic study of the association between long-term use of lithium and risk of upper urinary tract cancer, including renal cell cancer and cancers of the renal pelvis or ureter. We identified all histologically verified upper urinary tract cancer cases in Denmark … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
30
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 42 publications
4
30
0
1
Order By: Relevance
“…[5][6][7] Recently, two studies also reported an increased incidence of solid renal tumors in chronic lithium users compared with the general population. 8,9 However, because of several limitations of these studies as outlined by Licht et al 10 and contradictory findings in the study from Pottegård et al, 11 which included many more patients, we will not regard renal tumor development as a side effect of lithium treatment at this point. 10,11 In contrast to these adverse effects of lithium treatment, accumulating evidence suggests that the administration of low lithium amounts (,0.6 mM in blood) improves kidney function in different animal nephropathy models.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…[5][6][7] Recently, two studies also reported an increased incidence of solid renal tumors in chronic lithium users compared with the general population. 8,9 However, because of several limitations of these studies as outlined by Licht et al 10 and contradictory findings in the study from Pottegård et al, 11 which included many more patients, we will not regard renal tumor development as a side effect of lithium treatment at this point. 10,11 In contrast to these adverse effects of lithium treatment, accumulating evidence suggests that the administration of low lithium amounts (,0.6 mM in blood) improves kidney function in different animal nephropathy models.…”
mentioning
confidence: 97%
“…8,9 However, because of several limitations of these studies as outlined by Licht et al 10 and contradictory findings in the study from Pottegård et al, 11 which included many more patients, we will not regard renal tumor development as a side effect of lithium treatment at this point. 10,11 In contrast to these adverse effects of lithium treatment, accumulating evidence suggests that the administration of low lithium amounts (,0.6 mM in blood) improves kidney function in different animal nephropathy models. Single-bolus injections or short-term treatment (,1 week) of lithium reduced adriamycin-, LPS-, cisplatin-, gentamicin-, and ischemiainduced AKI, [12][13][14][15][16][17][18] whereas prolonged treatment ($1 month) alleviated kidney damage because of ischemia-reperfusion, hypertension, and the autoimmune disease lupus erythematosus.…”
mentioning
confidence: 97%
“…Lithium has been the main mood stabilizing treatment for bipolar disorder for more than 60 years and the evidence for its prophylactic effect is strong and still increasing . However, recently, clinicians and researchers were alarmed by findings from a small case‐series study suggesting an up to tenfold increased prevalence of renal cancer among long‐term lithium users . By contrast, the results from a subsequent Danish nationwide, population‐based case‐control study found no increased risk of renal or upper urinary tract cancer associated with lithium .…”
mentioning
confidence: 99%
“…Such misclassification is of particular importance when a carcinogenic effect of limited exposure needs to be assessed. Conversely, when only distant or very long-term drug use is anticipated to influence cancer risk, restriction to new users may hinder a meaningful evaluation [7].…”
Section: Considerations For the Choice Of Study Designmentioning
confidence: 99%
“…Clear associations have been established for a number of drugs, for example, the preventive effect of aspirin use against colorectal cancer [1,2] or the increased risk of renal cancer with use of phenacetin [3,4]. Further, new hypotheses often arise, such as the recent concerns about carcinogenic effects of lithium [5][6][7] and pioglitazone [8][9][10][11][12]. A significant challenge in the elucidation of drug effects on cancer development is that the effects typically first become manifest several years after drug initiation.…”
mentioning
confidence: 99%